2019
DOI: 10.1103/physreve.99.052106
|View full text |Cite
|
Sign up to set email alerts
|

Powerful harmonic charging in a quantum battery

Abstract: We consider a harmonic charging field as an energy charger for the quantum battery, which consists of an ensemble of two-level atoms. The charging of noninteracting atoms is completely fulfilled, which exhibits a substantial improvement over previous static charging fields. Involving the repulsive interactions of atoms, the fully charging is achieved with shorter charged period over the noninteracting case, yielding an advantage for the charing. Excluding the charging field, a quantum phase transition is induc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
120
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 146 publications
(122 citation statements)
references
References 24 publications
2
120
0
Order By: Relevance
“…In recent years, with the development of quantum thermodynamics and growing demand for device miniaturization, the quantum battery (QB), as a quantum energy storage device, has been receiving increasing attention. [ 1–17 ] The QB's energy storage is known to be a charging process, where the state of the system is transferred from a low energy level to a high energy level. In general, the battery pack system comprises many battery units to supply adequate energy.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…In recent years, with the development of quantum thermodynamics and growing demand for device miniaturization, the quantum battery (QB), as a quantum energy storage device, has been receiving increasing attention. [ 1–17 ] The QB's energy storage is known to be a charging process, where the state of the system is transferred from a low energy level to a high energy level. In general, the battery pack system comprises many battery units to supply adequate energy.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that choosing the proper type of charging field plays an important role in reducing the charging time. [ 9,10,12,13,18 ] For example, charging with a harmonic driving field is more efficient than charging with a steady one. [ 8,13 ] In addition, a charging process that contains entangling operations has a collective quantum advantage, where the charging speed increases with the number of battery units.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations